Relevance and Responsiveness of the Bachelor of Science in Customs Administration Program as Assessed by Stakeholders - Balajadia, Ruth (JPAIR Multidisciplinary Research, 2023)
Responsiveness/relevance is perceived as the starting point for determining what constitutes a quality education. Since development is necessary, systems that support development, like education and training systems, must be responsive. This study is focused on the relevance and responsiveness of the Bachelor of Science in Customs Administration (BSCA) program and to determine whether the initiatives currently practiced by the college to make the program relevant/responsive are effective. John B. Lacson Colleges Foundation-Bacolod is a higher education institution that offers a BSCA program and is the only one in Negros Occidental. However, despite the very satisfactory results in the board examination in the past years and the high demand for employment in the import and export industry, only a few are enrolled in the program. Hence, the conduct of this study is to explore opportunities to improve enrolment.  This descriptive study used the survey method to gather the data needed, with Mean and Standard Deviation as statistical tools. A discussion with representative stakeholders was made on the initiatives and strategies practiced by the college to calibrate the program. The respondents were 24 BSCA students, 53 alumni, and 22 industry representatives. The findings showed that the BSCA program is relevant and responsive to a very great extent, as assessed by the alumni and students, and relevant/responsive to a great extent by the industry.
Keywords: Education; relevance and responsiveness; customs administration; stakeholders; curriculum; descriptive design; Cebu Philippines